The portrayal of diabetes in the Indonesian online press: a corpus-based discourse study - Restu Santyarini; Muchamad Sholakhuddin Al Fajri (Cogent Arts & Humanities)
Diabetes poses a substantial public health concern in Indonesia, standing as the third leading cause of mortality following stroke and heart disease. The media holds potential as a crucial tool for public education, influencing perceptions of health issues and dispelling stigmatization or misinformation surrounding individuals with diabetes. This article investigates the representation of diabetes in Indonesian online news articles by drawing on a corpus-assisted discourse studies framework. The study focuses on analyzing nominal and verbal collocates of diabetes. The findings reveal prevalent collocations, such as penderita (sufferer), pasien (patient) and penyakit (disease), which carry stigmatizing and derogatory connotations. Additionally, the study finds a predominant emphasis on behavioral discourses in discussions about diabetes, potentially contributing to societal stigmatization, while neglecting structural or societal representations. The media’s inclination toward individualized narratives may be driven by considerations of newsworthiness and a perceived need to enhance public awareness regarding behavioral actions linked to diabetes. The study emphasizes the importance of achieving a more balanced coverage of diabetes in Indonesian news media. Integrating portrayals that highlight structural issues into news narratives is crucial for fostering a comprehensive understanding, garnering public support for societal-level policy changes and reducing the stigma associated with people with diabetes.